Canine decontamination, a laboratory study evaluating proper techniques to remove toxic materials from working dogs - France, Brian; Malloy, Thomas A.; Buntz, Robert G.; Mann, Kelly A. (Frontiers in Veterinary Science, 2025)
IntroductionWorking dogs can inadvertently encounter toxic chemicals while performing their key activities. These can include toxic industrial chemicals and materials (TICs/TIMs), pharmaceuticals, illicit drugs, sewage, pesticides, and even highly toxic chemical warfare agents. All these materials can poison the canine, be spread by touch, and can be transferred to the handler, vehicle, or veterinary medical staff. A successful decontamination technique must be safe for the handler to perform, can be performed at the site of contamination, successfully removes the hazardous material before it poisons the canine or transfers to other surfaces, and does not lead to a large hazardous waste disposal event.MaterialsCanine cadaver tissue samples (intact skin/fur) were used to conduct a decontamination comparison between dry, waterless, wipe decontamination and traditional soap and water wash decontamination. The chemical warfare agents sulfur mustard (HD) and venomous agent X (VX) were used for all testing.ResultsThe dry, waterless, wipe decontamination removed more chemical toxin (HD and VX) from canine fur, preventing transfer to the skin. The soap and water wash decontamination provided a route of transfer for toxins to reach the canine skin.DiscussionTo successfully decontaminate a working dog after toxic chemical exposure to HD and VX, dry, waterless, wipe decontamination should be performed to remove the majority of the toxin. This procedure reduces the transfer hazard to the handler, vehicle and veterinary medical staff which can then perform further decontamination and medical intervention.